Effects of environmental and growth conditions on protein produced by Bacillus subtilis ATCC21332 in the presence of Cymbopogon flexuosus essential oil - Noor H.M.; Alhadi N.A.; Mohamed H.S.; Radzi S.M.; Maryam Mohamed Rehan (Malaysian Society of Applied Biology, 2024)
Indexed by SCOPUS